Meta analysis of Masquelet technology and Llizarov technology in the treatment of infectious bone defects - Hao-Tian Hua (Journal of Hainan Medical University, 2020)
Objective: To systematically evaluate the clinical efficacy and safety of Masquelet technology and Llizarov group technology in the treatment of infectious bone defects by meta-analysis. Methods: The computer searched China Knowledge Network (CNKI), Wanfang, VIP, Chinese Biomedical Literature Database (CBM), Pubmed, Medline, Cochrane Llibrary databases. The retrieval time was from the time of the establishment of the database to January 2020. According to the inclusion and exclusion criteria, randomized controlled trials on the treatment of infectious bone defects using Masquelet technology and Llizarov technology were collected, and the retrieved literature was independently screened, evaluated, and data extracted by two researchers, and then RevMan5.3 software was used so for meta-analysis. Results: A total of 10 RCT documents were included, with a total of 496 patients, including 242 in the Masquelet group and 254 in the Llizarov group. The results of the meta-analysis showed that: in terms of bone defect healing time, total weight bearing time, treatment cost, and complication rate, the Masquelet group was significantly different from the Llizarov group, and the Masquelet group was better than the Llizarov group (P <0.05); In terms of knee joint Lowa score and SF- 36 score, Masquelet group has significant differences compared with Llizarov group, Llizarov group is better than Masquelet group (P <0.05); in excellent rate, number of operations, ankle Lowa score, infection control rate In terms of excellent rate of affected limb function, there was no significant difference between Masquelet group and Llizarov group (P> 0.05). Conclusion: Compared with Llizarov technology, Masquelet technology has obvious advantages in the treatment of infectious bone defects in terms of bone defect healing time, total weightbearing time, treatment cost, and complication rate. In terms of scoring, it has advantages over Masquelet technology, but in terms of excellent treatment rate, number of operations, and ankle lowa score. In terms of infection control rate and excellent function of affected limbs, there was no significant difference between Masquelet technology and Llizarov technology,However, due to the low quality of the included studies and the small sample size, the exact efficacy still needs to be confirmed by higher quality RCT studies.